Economic Analysis of Illegal Settlements in Flood Prone Areas in Palangkaraya City in Indonesia: A General Equilibrium Approach - Yuzuru Miyata; Hiroyuki Shibusawa; Indrawan Permana (European Regional Science Association (ERSA), 2014)
Since initially steaming from von Thünen's work (1826), bid-rent approach has been rigorously applied to analyze land use configuration. Alonso (1964), Muth (1969), Beckman (1973), Solow (1973), and Fujita (1989) are among the scientists who greatly contributed to forward von Thünen's theory into complexities in urban context.. Particularly Fujita (1989) has showed solution of a utility optimizing problem to define the bid-rent function which gives the maximum ability of households to pay land under a fixed utility and at distance from the Central Business District (CBD). The bid rent concept provides richer analysis of the locational choice of households in the city. Our study considered a small-medium city in a developing country located in tropics where a massive deforestation and river flood significantly jeopardize some areas in the city. It is Palangkaraya city in Central Kalimantan province, Indonesia. There are two types of land classified in the city. One is called normal land where the river flood is not able to inundate while another one is namely flood prone areas. The flood prone areas are occupied by settlements which are mostly illegal. Here illegal settlement refers to those kinds of settlements which were built on parcels with no legal clearance on land ownership including those which were constructed without building permission (Kapoor &Blanc, 2008). This paper aims to analyze a configuration of the residential land use pattern in Palangkaraya city in Indonesia applying bid-rent approach which incorporated the expected flood damage rate (EFDR) on household assets. The EFDR is employed to predict the damage by the river flood since flood occurrences are stochastic and such appropriate data on flood occurrences is not available. Previously Permana and Miyata (2009) showed a partial equilib-rium urban economic model, introducing the EFDR. However we realize that the partial equilibrium model slightly lack of reality since income is assumed to be exogenously given. Hence we develop a general equilibrium model taking into account firms in the Central Business District (CBD), and by incorporating the expected damage rate on household's asset, the new bid rent function and bid max lot size function are obtained. Applying the general equilibrium modeling approach, one can derive the conclusion that the bid rents by low income households get higher than those by high income households in flood prone areas. This is the contrary conclusion being highlighted as compared with that in the traditional urban economics.
Keywords: R13; R14; O18; D50; Q54; Q56; 330; Bid-Rent Approach; General Equilibrium Model; illegal settlements; flood prone area; Palangkaraya City; Indonesia